TREND IN PHYSICAL ACTIVITY LEVELS AMONG CHILDREN AGED 11 TO 14 - Đošić, Anđela; Živković, Danijela; Purenović-Ivanović, Tijana; Ranđelović, Nebojša; Pantelić, Saša (Physical Education and Sport Through The Centuries, 2024)
The research assessed the level of physical activity (PA) of boys and girls aged 11-14, as well as trends in PA levels. The sample included a total of 433 children aged 11-14, comprising 238 boys and 195 girls. PA was assessed using the FELS questionnaire, which included questions about the frequency of PA in sports, PA during leisure time, PA at home, and overall PA. To determine the trend in PA levels across specific domains and overall, trend analysis was applied, followed by comparisons using the LSD Post Hoc Test. Data were processed using the SPSS statistical package (p < .05). The results showed that boys had significantly higher levels of PA across all periods compared to girls. Significant changes in PA levels among boys were observed in the domain of PA in sports (Sig. = < .001) and overall PA (Sig. = .008). A significant decline in PA in sports among boys was noted between the ages of 11 and 13, as well as between 11 and 14 years, while the decline in overall PA was observed between the ages of 11 and 13. Among girls, a decline in PA in the domain of household chores was identified between the ages of 11 and 14. In the domain of overall PA, significant decreases were observed between the ages of 11 and 13, 11 and 14, 12 and 13, and 12 and 14. It was found that PA among children aged 11-14 significantly decreases around the ages of 12 and 13. Efforts should focus on promoting PA within this population group and identifying appropriate strategies to increase or at least maintain PA levels during this critical period.